2014
DOI: 10.1016/j.pain.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Human sensory neurons: Membrane properties and sensitization by inflammatory mediators

Abstract: Biological differences in sensory processing between human and model organisms may present significant obstacles to translational approaches in treating chronic pain. To better understand the physiology of human sensory neurons, we performed whole-cell patch-clamp recordings from 141 human dorsal root ganglion (hDRG) neurons from five young adult donors without chronic pain. Nearly all small diameter hDRG neurons (<50 μm) displayed an inflection on the descending slope of the action potential, a defining featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
188
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(206 citation statements)
references
References 56 publications
17
188
0
1
Order By: Relevance
“…However, these effects are generally seen in DRG neurons in culture for several days. As described in MATERIALS AND METH-ODS, our preliminary experiments indicated that supplements of these trophic factors were necessary to obtain viable human DRG neurons for recordings, in agreement with recently published data (Davidson et al 2014); thus both NGF and GDNF were added into the primary human DRG culture. Therefore it is possible that differences in exposure to NGF and/or GDNF could have contributed to the different firing behavior that we observed between human and rat DRG neurons.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, these effects are generally seen in DRG neurons in culture for several days. As described in MATERIALS AND METH-ODS, our preliminary experiments indicated that supplements of these trophic factors were necessary to obtain viable human DRG neurons for recordings, in agreement with recently published data (Davidson et al 2014); thus both NGF and GDNF were added into the primary human DRG culture. Therefore it is possible that differences in exposure to NGF and/or GDNF could have contributed to the different firing behavior that we observed between human and rat DRG neurons.…”
Section: Discussionsupporting
confidence: 86%
“…The mean input resistance (153 Ϯ 20 M⍀) and action potential threshold (964 Ϯ 85 pA) of human DRG neurons are different from the input resistance (659 Ϯ 51 M⍀) and threshold for action potential (251 Ϯ 29 pA) for native rat DRG neurons but are comparable to those reported by Davidson et al (2014) from a different set of human donors (input resistance: 97.51 Ϯ 10.09 M⍀; threshold: 1,430 Ϯ 110 pA), confirming that these properties are intrinsic to human DRG neurons. The action potential width in human DRG neurons (6.83 Ϯ 0.78 ms) was threefold greater than that of rat DRG neurons (2.33 Ϯ 0.12 ms), and human DRG neurons manifested increased firing frequencies compared with rat DRG neurons.…”
Section: Discussionsupporting
confidence: 69%
“…Upon the delivery, DRGs were rapidly dissected from nerve roots and minced in a calcium-free HBSS (Gibco). Human DRG cultures were prepared as previously reported with some modifications 46, 47 . DRGs were digested at 37°C in humidified O 2 incubator for 120 min with collagenase Type II (Worthington, 285 units/mg, 12 mg/ml final concentration) and dispase II (Roche, 1 unit/mg, 20 mg/ml) in PBS with 10 mM HEPES, pH adjusted to 7.4 with NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…Such investigations are important for translation of findings made in rodents to humans (see Davidson et al 2014).…”
mentioning
confidence: 99%